(untitled) (Journal Of Educational and Psychological Researches, 2016)
study aimed to recognize the relationship shyness and depression and to recognize the differences between the genders, according to the variable of shyness and depression, the sample consisted (214) students, (141) female (73) male, and the sample responded scale of shyness and Inventory beck for depression, The Results of this study show that: the sample has a low degree shyness and a high degree depression, . There are no statistically significant differences according to gender variable in shyness, and there are statistically significant differences according to gender variable in depression favor for male, and there are statistically significant relationships between the variables of the study at level (0.01)